Teun A. Van Dijk Discourse Analysis of Social Issues in the song “know Your Enemy” and “21Guns” by Green Day - Natalino Alvares Talalab; Suhartawan Budianto (Menulis: Jurnal Penelitian Nusantara, 2025)
Social issues are often represented and maintained through discourse, reflecting and reinforcing the existing power structures and inequalities in society. The thesis writer use method Qualitative design, qualitative research allows for in-depth exploration of phenomena in natural settings, providing rich and detailed insights into the subject matter. In collecting data in the study using 4 stages, among others, selection of song, collection of lyrics, review of lyrics, contextual information. the research results obtained are in the Lyrics songs "know your enemy" emphasizes themes of awareness, rebellion, and resistance against oppressive systems, while "21 Guns" songs portrays themes of emotional struggle, loss, and the search for peace. Language and Power In "Know Your Enemy," repetition and imperative language create a call to action, urging listeners to recognize and oppose systemic oppression. "21 Guns" employs metaphor and rhetorical questions to engage listeners in a reflective dialogue about the cost of conflict and resistance. Ideological perspectives from this song that challenge authoritative power and advocate for social awareness. "Know Your Enemy" aligns with anti-authoritarian and anti-establishment ideologies, reinforcing the importance of recognizing and resisting control. "21 Guns" takes a more introspective approach, questioning the consequences of violence and encouraging reconciliation.